Особливості побудови гетерогенних мереж - Гонтар, І. Ю. (ХНУРЕ, 2024)
It is shown that the development of the concept of heterogeneous networks is due to an increase in bandwidth due to the mechanisms of spatial compaction and spectral aggregation. The architecture and basic properties of the HetNet network are analysed. It is proved that the efficient simultaneous use of several RATs is one of the key tasks of HetNet. The main approaches to coordinating the joint work of different RATs are presented. It is shown that the network optimisation is possible due to more advanced methods of radio resource allocation between the RATs.
Keywords: побудова гетерогенних мереж; HetNet network